Comparison Between Digital Subtraction Angiography And Magnetic Resonance Angiography In The Investigation Of Acute Ischemic Stroke In A Tertiary Care Hospital In Bangladesh (Bangladesh Journal of Medicine, 2023)
Background: Ischemic stroke is the most common type of stroke. Digital subtraction angiography (DSA) is a definite method for demonstrating vascular lesions, while High-resolution Magnetic Resonance Angiography (MRA) imaging has recently been introduced as a promising diagnostic modality in intra-cranial artery disease. This study aimed to compare between DSA and MRA as the modality of investigation of ischemic stroke.Methods: This quasi-experimental study was conducted at the department of Neurology, Sir Salimullah Medical College & Mitford Hospital, Dhaka, for one year following ethical approval. Total of 30 patients with acute ischemic stroke were enrolled in this study. DSAs and MRAs of all patients were analyzed and reported by two experienced neurologists. Collected data will be recorded into the separate case-record form and analyzed by SPSS 24.Results: The mean age of the studied respondents was 47.50±10.42 (SD) years with male predominance (63.3%).Among the male patients, 73.7% were smoker and female patients 81.8% were non-smoker. Among the total patients 80.0% had HTN and 73.3% DM, 24.1% had history of other cardio-vascular diseases and 36.7% of the patients had family history of stroke. Maximum patients had arm weakness (66.7%), leg weakness (60.0%), self-reported speech disturbance (53.3%) and dysphasia or dysarthria (53.3%). Hypertension and diabetes mellitus were present in 80% and 73.3% cases, respectively. For the majority of the patients the affected artery was MCA (Middle cerebral artery) and it was among 17 out of 30 patients. The aetiology based on TOAST diagnosis was similar by both MRA and DSA in 16 (out of 30). All the DSAs and 22 out 30 MRAs revealed abnormalities.Conclusion: MRA has significant agreement with DSA to identify etiology of acute ischemic stroke. Hence, it is better to use MRA in ischaemic stroke considering its non-invasiveness and cost-effectiveness.Bangladesh J Medicine 2023; 34(2): 126-132